Metallic State in Cubic FeGe Beyond Its Quantum Phase Transition - Pedrazzini, Pablo; Pedrazzini, P.; Wilhelm, H.; Jaccard, D.; Jarlborg, T.; Schmidt, M.; Hanfland, M.; Akselrud, L.; Yuan, H. Q.; Schwarz, U.; Grin, Yu.; Steglich, F. (American Physical Society, 2007)
Fil: Pedrazzini, P. Comisión Nacional de Energía Atómica. Instituto Balseiro, Argentina; University of Geneva; Suiza